A systematic review on efficacy, safety, and treatment-durability of low-dose rituximab for the treatment of Pemphigus: special focus on COVID-19 pandemic concerns. (3rd September 2021) - Tavakolpour, Soheil; Aryanian, Zeinab; Seirafianpour, Farnoosh; Dodangeh, Milad; Etesami, Ifa; Daneshpazhooh, Maryam; Balighi, Kamran; Mahmoudi, Hamidreza; Goodarzi, Azadeh
Abstract: Background: Rituximab is a FDA-approved monoclonal antibody for adults with moderate to severe potentially life-threatening pemphigus vulgaris. Recent studies have focused on assessments of efficacy and safety of low-dose rituximab (<2 gram in each cycle). Method: Databases were searched from 2010 to 2020 (last update: 1 June 2020). Result: Nine studies were entered; including180 cases (92: women, 88: men, age range: 9–83 years). The dosages of each Rituximab cycle varied between ultra-low-dose (≤500 mg for a cycle, either multiple infusions or a single infusion), low-dose (2 × 375 mg/m 2 or 2 × 500 mg) and modified-dose (3 × 375 mg/m 2 or 3 × 500 mg). The efficacy and safety of Rituximab in the studies are known by the recovery time, relapse time, and side events. According to the studies, 2 × 500 can lead to complete remission in a broad range, from 35 to 82%. These differences might be explained by different end-points and variable cumulative corticosteroid dosage after RTX administration. Although the studies showed that low dose RTX is efficient, there are some controversies regarding the choosing low-dose for severe patients. Conclusion: Considering the effectiveness of low-dose, intermediate dose, and ultra-low-dose protocols of Rituximab in inducing remission in pemphigus disease and considering factors such as cost of therapy, and the need to induce a minimum of immunosuppression for a minimum duration in the COVID-19 pandemic, suggested to use low-dose Rituximab protocol (2 infusions of 500 mg Rituximab: interval of 2 weeks) to induce the remission in mild-to-moderate pemphigus patients.